Pomoč nadarjenim učencem pri soočanju s težavami na socialnem in emocionalnem področju v sodelovanju s šolsko knjižnico - Vernig, Manca (Šolska knjižnica, 2014)
Talented students can have many problems in the social and emotional areas, and these problems in many cases differ from the problems of their peers. They often experience difficulties in building relationships, feelings of loneliness, even alienation, or try to keep their talent hidden to adapt to the group. Due to their high-level achievements they can be expected to always be successful in all areas which can lead to exhaustion, stress, perfectionism or feelings of guilt. In order to successfully address their problems the talented students need help, part of which can also be the school library. One of potential activities which help the talented address their social and emotional problems is bibliotherapy which can be performed by the school librarian.
Keywords: biblioterapija; nadarjeni učenci; nadarjenost; šolske knjižnice